THE INFLUENCE OF SOCIAL CAPITAL AND PSYCHOLOGY CAPITAL ON ENTREPRENEURIAL INTENTION WITH ENTREPRENEURIAL ORIENTATION AS A MEDIATING VARIABLE IN VOCATIONAL EDUCATION STUDENTS AT MAN 1 BUKITTINGGI - Anwar, Kendis; Sari, Nadhila; Friyatmi, Friyatmi; Evanita, Susi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
New business growth is significantly influenced by entrepreneurial intention. Although numerous research have demonstrated that attitudes have an impact on how intentions are formed, little has been done to dynamically engage social and psychological capital in this interaction. An essential part of developing trustworthy and competent human resources in this industry is vocational education. The purpose of this study is to ascertain the relationship between social capital and psychological capital on entrepreneurial intention and to investigate the mediation function of entrepreneurial orientation in that relationship. This research uses quantitative research methods. Data was collected through an online questionnaire which was filled in by vocational education students at MAN 1 Bukittinggi. The number of samples in this study were 101 students. The data collection technique used in this study was a questionnaire which was analyzed using Structural Equation Modeling (SEM) with the Smart PLS analysis tool. The results showed that social capital and psychological capital had no significant effect on entrepreneurial intentions, but had a significant effect on entrepreneurial orientation, which in turn had a significant effect on entrepreneurial intentions. Finally, social capital and psychological capital have a significant effect on entrepreneurial intentions through the mediation of entrepreneurial orientation.